Butyric Acid Modulates Gut Microbiota to Alleviate Inflammation and Secondary Bone Loss in Ankylosing Spondylitis - Ke You; Lianjun Yang; Zhihai Su; Jun Shen; Xinyang Fan; Yuanqing Guo; Zhen Yuan; Hai Lu (Biomedicines)
Background: Ankylosing spondylitis (AS) is a chronic inflammatory and autoimmune disease that primarily affects the sacroiliac joints and axial skeleton. While the exact pathogenetic mechanism of AS remains unclear, previous reports have highlighted the involvement of genetic factors, immune responses, and gut microbiota dysregulation in the development of this condition. Short-chain fatty acids (SCFAs), which are microbial fermentation products derived from sugar, protein, and dietary fibers, play a role in maintaining the intestinal barrier function and reducing inflammatory responses. The aim of this study was to investigate the therapeutic potential of butyric acid (BA), an important SCFA, in the treatment of AS. Methods: To evaluate the anti-inflammatory and anti-bone loss effects of BA, a murine AS model was established using proteoglycan and dimethyl dioctadecyl ammonium (DDA) adjuvants. Various techniques, including an enzyme-linked immunosorbent assay (ELISA), magnetic resonance imaging (MRI), micro-CT, histology, quantitative PCR (qPCR) for intestinal tight junction protein expression, and 16S rDNA sequencing to analyze gut microbiota abundance, were employed to assess the inflammation and bone health in the target tissues. Results: The results indicated that BA demonstrated potential in alleviating the inflammatory response in the peripheral joints and the axial spine affected by AS, as evidenced by the reductions in inflammatory infiltration, synovial hyperplasia, and endplate erosion. Furthermore, BA was found to impact the intestinal barrier function positively. Notably, BA was associated with the downregulation of harmful inflammatory factors and the reversal of bone loss, suggesting its protective effects against AS. Conclusions: These beneficial effects were attributed to the modulation of gut microbiota, anti-inflammatory properties, and the maintenance of skeletal metabolic homeostasis. This study contributes new evidence supporting the relationship between gut microbiota and bone health.